2023
DOI: 10.3390/nano13131925
|View full text |Cite
|
Sign up to set email alerts
|

GO/CNT−OH/Nafion Nanocomposite Humidity Sensor Based on the LC Wireless Method

Chengkai Wang,
Chunxiao Jiao,
Meng Wang
et al.

Abstract: In recent years, LC resonant sensors have gained widespread attention for their extensive applications in industries such as pharmaceutical storage and food transportation. A wireless passive sensor with a good sensing performance is proposed based on a GO/CNT−OH/Nafion nanocomposite. The sensor was fabricated via inkjet printing technology, and the surface morphology of the GO/CNT−OH/Nafion nanocomposite was characterized by SEM measurement. It is found that the MWCNTs support the GO layer and the hydrophobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…GO can be chemically modified and its affinity with water molecules can be used to make humidity sensors. 124 Previous studies have shown that water embedding in 2D material layers can significantly improve the response time and sensitivity of GO. For example, at 40% relative humidity (RH), the response time of GO nanocomposite is 82.67 times that of normal conditions, and its sensitivity is 95.7 times that of normal conditions at 60%RH.…”
Section: Applications Of Biomedical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…GO can be chemically modified and its affinity with water molecules can be used to make humidity sensors. 124 Previous studies have shown that water embedding in 2D material layers can significantly improve the response time and sensitivity of GO. For example, at 40% relative humidity (RH), the response time of GO nanocomposite is 82.67 times that of normal conditions, and its sensitivity is 95.7 times that of normal conditions at 60%RH.…”
Section: Applications Of Biomedical Applicationsmentioning
confidence: 99%
“…found that the GO humidity sensor has a frequency change of 103 kHz/%RH at low humidity (30–60%RH). 124 In addition, Wu et al. demonstrated that a GO-based humidity sensor has ultra-high sensitivity at room temperature, with a response time of 3 s faster than normal conditions and a wide detection range of 8–95% RH.…”
Section: Applications Of Biomedical Applicationsmentioning
confidence: 99%